Arabic translation and psychometric testing of the prenatal eating behaviors screening tool - John Paul Ben Silang; Fathima Minisha; Hayat Qassim A-Hajjaji; Catherine Medina Lim; Jishamol Thankappan; B’Chira Bent Ismail Ben Ali; Mani Megalai Prakash; Zeinab Abdillahi Mohamed; Remya Mathew; David Hali De Jesus; Salwa Mohammad Abu Yaqoub; Thomas Farrell (Journal of Eating Disorders)
Abstract Background Early detection and treatment of eating behavioral problems among pregnant women are essential due to the associated adverse impact on pregnancy and the health of the offspring. Prenatal Eating Behaviors Screening (PEBS) tool, a 12-item self-administered questionnaire, can be used to screen for eating disorders (ED) during pregnancy. This study performed an Arabic translation of PEBS and a psychometric analysis to determine its validity and reliability. Methods The standard forward-backward translation method was used to generate PEBS-Arabic. The 12-item Likert scale questionnaire was completed by 116 antenatal women in the tertiary maternity care hospital in Qatar. Content validity was determined by the content validity index (CVI) using input from five experts. Reliability was assessed using Cronbach’s alpha, and confirmatory and exploratory factor analysis (CFA & EFA) to test construct validity. The correlations between PEBS-Arabic scores and maternal characteristics were explored. Results The mean total PEBS score in the cohort was 16.3 (± 5.2), with nulliparity and higher educational level resulting in statistically significantly higher mean scores. The PEBS-Arabic had a very good item-CVI and scale-CVI of 1.00. The overall Cronbach’s alpha was 0.77, which demonstrated good and acceptable reliability. The CFA using a single-factor solution showed an acceptable correlation for most items. In the EFA, a two-factor solution resulted in most items loading accurately into the pre-determined factors (bulimia and anorexia) with acceptable correlations. Conclusion The PEBS-Arabic is the first translated version of this pregnancy-specific screening tool for ED. This tool demonstrates good reliability, content and construct validity. This study is a valuable step towards understanding and detecting the prevalence and determinants of ED in pregnancy, with the aim of improving maternal, fetal and child health.